Imaging, multi-scale, and high contrast partial differential equations - Seoul ICM 2014 Satellite Conference, Imaging, Multi-scale and High Contrast PDEs (Daejeon, Korea 7-9 Aug 2014); Ammari, Habib; Capdeboscq, Yves; Kang, Hyeonbae; Sim, Imbo (Providence : American Mathematical Society, 2016)
This volume contains the proceedings of the Seoul ICM 2014 Satellite Conference on Imaging, Multi-scale and High-Contrast PDEs, held from August 7-9, 2014, in Daejeon, Korea. The mathematical analysis of partial differential equations modelling materials, or tissues, presenting multiple scales has been a very active area of research. The study of the corresponding imaging or reconstruction problem is a more recent area. If the material parameters of the partial differential equation present high contrast ratio, then the solution to the PDE becomes particularly challenging to analyze and compute. On the other hand, imaging in highly heterogeneous media poses significant challenges to the mathematical community. The focus of this volume is on recent progress towards complete understanding of the direct problem with high contrast or high frequencies, and unified approaches to the inverse and imaging problems for both small and large contrast or frequencies. Of particular importance in imaging are shape representation techniques and regularization approaches. Special attention is devoted to new models and problems coming from physics leading to innovative imaging and signal processing methods.
Includes bibliographical references.
Keywords: Partial differential equations -- Congresses; Signal processing -- Congresses